2014
DOI: 10.15288/jsad.2014.75.476
|View full text |Cite
|
Sign up to set email alerts
|

The Transition to Medication Adoption in Publicly Funded Substance Use Disorder Treatment Programs: Organizational Structure, Culture, and Resources

Abstract: ABSTRACT. Objective: Medications for the treatment of substance use disorders (SUDs) are not widely available in publicly funded SUD treatment programs. Few studies have drawn on longitudinal data to examine the organizational characteristics associated with programs transitioning from not delivering any pharmacotherapy to adopting at least one SUD medication. Method: Using two waves of panel longitudinal data collected over a 5-year period, we measured the transition to medication adoption in a cohort of 190 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…189 Regarding the uptake of MAT, a study among a U.S. cohort of 190 publicly-funded treatment organizations that offered no substance use disorder (SUD) medications at baseline showed that 23% offered SUD medications after five years of follow-up. 190 This was more likely to occur in programs that had greater medical resources, Medicaid funding, and contact with pharmaceutical companies. 190…”
Section: Medication Assisted Treatment (Mat) For Heavy Drinking and Audmentioning
confidence: 99%
“…189 Regarding the uptake of MAT, a study among a U.S. cohort of 190 publicly-funded treatment organizations that offered no substance use disorder (SUD) medications at baseline showed that 23% offered SUD medications after five years of follow-up. 190 This was more likely to occur in programs that had greater medical resources, Medicaid funding, and contact with pharmaceutical companies. 190…”
Section: Medication Assisted Treatment (Mat) For Heavy Drinking and Audmentioning
confidence: 99%
“…Medicaid revenues are positively associated with both the adoption (i.e., any use) and implementation (i.e., extent of use) of such medications (35, 36). Comparisons of privately funded treatment programs to those that rely on governmental grants and contracts have revealed sizeable differences in adoption of medications (36, 37), while the percentage of patients insured by health maintenance organizations (HMOs) is positively associated with the adoption of naltrexone (38). These studies suggest that Medicaid and private insurance revenues may be associated with smoking cessation pharmacotherapy.…”
mentioning
confidence: 99%
“…Of course broad-based legislation or policies are being evaluated, but using evaluation paradigms that do not follow the orthodox Campbellian model, but rather an econometric approach, for instance. (Gu et al, 2014; Greene et al, 2014; Abraham, 2014; Wagner et al, 2014, Knudsen and Roman, 2014). The problem is that such non-experimental evaluations would either not be eligible for inclusion or would rank low in a registers’ current rating schemes.…”
Section: Discussionmentioning
confidence: 99%